Profil perdarahan uterus abnormal di RSUP Prof. Dr. R. D. Kandou Manado periode 1 Januari 2013 â€“ 31 Desember 2014 - Rifki, Muhammad; Loho, Maria; Wagey, Frank M.M (e-CliniC, 2016)
Abstract: Abnormal Uterine Bleeding (AUB) is the most common cause of abnormal vaginal bleeding among women in reproductive age. Approximately 30% of women come to health care center with complaints of AUB during their reproductive period. The causes of AUB include a broad spectrum of diseases. The main classification of AUB according to FIGO has 9 categories of causes that is the acronym as "PALM-COEIN". This was a descriptive retrospective study using data of medical records of patients with abnormal uterine bleeding. The results showed that of: 51 cases with AUB, most were at the age of 41-50 years (24 cases; 47.06%), with the youngest age was 14 years and the oldest age was 55 years. Most of the cases had normal body mass index, multiparity, and housewife. PALM-COEIN classification showed that most were leiomyoma (29 cases; 56.86%) and ovulatory dysfuntion (11 cases; 21.57%). Conclusion: Of the 51 patients with AUB at the Obstetrics and Gynecology Department of Prof. Dr. R. D Kandou Hospital Manado from January 2013 to December 2014, most cases were aged 41-50 years, multiparity, normal BMI, leiomyoma, treatment with D & C, and the pathological tesult was hyperplasia Keywords: abnormal uterine bleeding (AUB)Â Abstrak: Perdarahan Uterus Abnormal (PUA) merupakan penyebab tersering perdarahan abnormal per vaginam pada masa reproduksi wanita. Sekitar 30% wanita datang ke pusat pelayanan kesehatan dengan keluhan PUA selama masa reproduktif. Penyebab terjadinya PUA mencakup spektrum yang luas dari berbagai penyakit. Klasifikasi utama yang digunakan untuk PUA berdasarkan FIGO terdapat 9 kategori penyebab yaitu akronim dari â€œPALM-COEINâ€. Jenis penelitian ialah deskriptif retrospektif, dengan menggunakan data rekam medik pasien dengan PUA. Hasil penelitian memperlihatkan dari 51 kasus dengan PUA didapatkan paling sering pada usia 41-50 tahun sebanyak 24 kasus (47,06%), dengan usia termuda 14 tahun dan usia tertua 55 tahun. Kasus PUA terbanyak dengan Indeks Massa Tubuh normal, paritas multipara, dan pekerjaan sebagai Ibu Rumah Tangga. Klasifikasi penyebab dengan PALM-COEIN sebagian besar ialah jenis leiomioma sebanyak 29 kasus (56,86%) dan jenis ovulatory dysfuntion sebanyak 11 kasus (21,57%). Simpulan: Dari 51 kasus PUA di Bagian Obstetri dan Ginekologi RSUP Prof. R. D. Kandou Manado kurun waktu Januari 2013 sampai Desember 2014 ditemukan terbanyak pada usia 41-50 tahun, multipara, IMT normal, jenis PUA leiomioma, pengobatan D & C, dengan hasil PA hiperplasia.Kata kunci: perdarahan uterus abnormal (PUA)